921. Leveraging the Electronic Health Record for Antimicrobial Stewardship: Assessing the Impact of Antimicrobial Ordering Clinical Decision Support Tools on Duration of Therapy. (15th December 2022) - Gerhardt, Jenna; Cheatham, Megan; Davis, Christie M; Dine, Serena; Erdman, Sharon; Geik, Katherine; Gerke, Steven; Kressel, Amy B; McIntire, Allyson
Abstract: Background: In an ideal state, the stewardship of antimicrobial agents would happen at the point of order entry. In June 2018, Eskenazi Health implemented a series of clinical decision support tools in the electronic health record (EHR), including required fields on all inpatient antimicrobial orders for indication, type of therapy (empiric or definitive), and duration. When empiric therapy is selected, providers receive a Best Practice Advisory (BPA) at 48 hours to re-evaluate therapy. Additionally, a side bar table was added to all antimicrobials orders that included drug-specific duration of therapy recommendations for common indications. Methods: This is a single-center, retrospective, observational chart review that includes adult inpatients prescribed antibiotics for the treatment of CAP or UTI from July 2017 to December 2018. The primary outcome is the overall length of therapy between pre- and post-intervention groups for CAP and UTI. Secondary outcomes include duration of empiric/broad-spectrum therapy, duration of definitive therapy, time to de-escalation, length of hospital stay, C. difficile infections, 30-day readmission, and cost of antimicrobial therapy. Results: A total of 541 orders were included for analysis. The composite overall duration of therapy decreased from 7 days to 5 days in the post-intervention group (p< 0.001). For CAP, the duration of therapy (5 days) was not different between groups. For UTI, the duration of therapy decreased from 11 days to 7 days in the post-intervention group (p< 0.001). The duration of empiric therapy decreased from 3 days to 2 days (p< 0.001) and the duration of definitive therapy decreased from 4 days to 3 days (p< 0.001). There was a 1 day longer length of stay for patients in the post-intervention group (p=0.038); however, there was a lower 30-day readmission rate in the post-intervention group (p=0.003). The rate of hospital-acquired C. difficile infections did not differ between groups (p=1.000). It was found that action was taken from the BPA 55.4% of the time after implementation. Conclusion: The duration of therapy overall was shortened by 2 days, which was driven by the difference in duration for UTI. Incorporating antimicrobial stewardship principles at the point of order entry can result in fewer days of unnecessary therapy. Disclosures: All Authors : No reported disclosures.